Entrepreneurial innovations in Africa: agricultural challenges and food issues - (:unkn) unknown (My University, 2018)
Current academic research strongly suggests adapting models of analysis of entrepreneurial innovations to the specificity of African contexts. The purpose of this short note is to explore through an up-dated literature review of academic research and empirical applications, the question of entrepreneurial innovations in African. By extension, we will examine some possible links with agricultural challenges and future food issues.
Keywords: African Research